Energy resource management in smart home: state of the art and challenges ahead - Rathnayaka, Dinusha; Potdar, Vidyasagar; Kuruppu, S. (Springer, 2011)
Residential sector registers one of the highest energy consumers in the world; hence efficient Energy Resource Management (ERM) scheme has become essential in new home or renovation projects. Smart home concept is an appealing way to promote the ERM. According to the literature, diverse research efforts have been emerged to investigate the ERM in smart homes. However in order to succeed in future researches, it is imperative to realize the current position of the ERM in the smart home research field. A clear identification of gaps in existing literature would significantly benefit the new researchers to understand the challenges ahead. In this article, we critically discuss the state of the art and the open research issues of the ERM in smart home.